The Effect of Product Innovation on Consumer Interest in the Purchase of Bottled Tea Products at PT. Sinar Sosro Medan - Sarman Sinaga; Jonner Lumban Gaol; Reza Nurul Ichsan (Budapest International Research and Critics University, 2021)
Product innovation is a guideline that is expected to influence consumer interest in purchases. The problem formulation in this study is whether there is a significant influence of product innovation on consumer interest in purchasing. And the purpose of this research is to find out if there is a significant relationship between product innovation and consumer interest in purchasing Bottled Tea Products at PT Sinar Sosro Medan. The research approach carried out is a quantitative type of primary data source. This study used a simple linear regression analysis model using SPSS (Statistica Product and Service Solution) software version 21.0. The number of samples in this study was as many as 78 customers. The results of this study showed a regression equation where Y = 1,807 + 0.5X + e, which means product innovation has a positive influence on consumer interest. This indicates that if there is an increase in product innovation by 1 unit, it will be followed by an increase in consumer interest by 0.5 units. Based on the significance test shows a significant influence of product innovation on consumer interest, it is seen that the significance value for the influence of X on Y is 0.00<0.05 and thitung value of 5.626> ttabel 2.6403 means that if product innovation is improved then consumer interest will also increase. And from the test results of the coefficient of determination in nila R Square of 0.294 this shows that 29.4% of consumer interest is influenced by product innovation and the remaining 71.5% is influenced by other variables outside of this study. This will be even better if product innovation continues to be implemented and improved with the increasing interest of consumers, because of PT employees. Sinar Sosro will have the opportunity to channel its creativity with better innovation ideas.